The role of remote sensing in geothermal exploration :Powerpoint - Hecker, C.A. (University of Twente, 2020)
This lecture introduces: The role of remote sensing in geothermal exploration; Traditional exploration methods; Remote sensing of geothermal sites; Remote sensing: from hydro to geothermal – lessons learned future prospects.